A PariwiPARIWISATA ADAT PESISIR: EKSPLORASI NILAI-NILAI TRADISIONAL DALAM UPACARA NADRAN INDRAMAYU sata Adat Pesisir: Eksplorasi Nilai-Nilai Tradisional dalam Upacara Nadran Indramayu - Suhaeb, Isad; Eva Farhah (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2025)
The Nadran ceremony is an annual tradition among coastal communities in Indramayu, serving as an expression of gratitude to God for abundant marine harvests. This ritual reflects rich local cultural values such as social solidarity, maritime spirituality, and marine environmental preservation. This study aims to explore the traditional values embedded in the Nadran ceremony and its potential as a cultural tourism attraction. A qualitative approach was employed, using participatory observation, in-depth interviews, and visual documentation techniques. The findings reveal that Nadran functions not only as a religious ritual but also as a means of expressing the collective identity of coastal communities. Its potential as a cultural tourism attraction is significant if managed participatively and sustainably. The involvement of local communities in preservation efforts and the contextual packaging of the attraction are key to developing traditional tourism based on local values. These findings are expected to enhance understanding of the integration between local cultural preservation and sustainable tourism development in coastal areas.